The WiggleZ Dark Energy Survey: final data release and the metallicity of UV-luminous galaxies. Issue 3 (21st November 2017) - Drinkwater, Michael J; Byrne, Zachary J; Blake, Chris; Glazebrook, Karl; Brough, Sarah; Colless, Matthew; Couch, Warrick; Croton, Darren J; Croom, Scott M; Davis, Tamara M; Forster, Karl; Gilbank, David; et al.
Abstract: The WiggleZ Dark Energy Survey measured the redshifts of over 200 000 ultraviolet (UV)-selected (NUV < 22.8 mag) galaxies on the Anglo-Australian Telescope. The survey detected the baryon acoustic oscillation signal in the large-scale distribution of galaxies over the redshift range 0.2 < z < 1.0, confirming the acceleration of the expansion of the Universe and measuring the rate of structure growth within it. Here, we present the final data release of the survey: a catalogue of 225 415 galaxies and individual files of the galaxy spectra. We analyse the emission-line properties of these UV-luminous Lyman-break galaxies by stacking the spectra in bins of luminosity, redshift, and stellar mass. The most luminous (-25 mag<M_FUV<-22 mag ) galaxies have very broad Hβ emission from active nuclei, as well as a broad second component to the [O iii ] (495.9 nm, 500.7 nm) doublet lines that is blueshifted by 100 km s −1 , indicating the presence of gas outflows in these galaxies. The composite spectra allow us to detect and measure the temperature-sensitive [O iii ] (436.3 nm) line and obtain metallicities using the direct method. The metallicities of intermediate stellar mass (8.8 < log ( M * /M⊙ ) < 10) WiggleZ galaxies are consistent with normal emission-line galaxies at the same masses. In contrast, the metallicities of high stellar mass (10 < log ( M * /M⊙ ) < 12) WiggleZ galaxies are significantly lower than for normal emission-line galaxies at the same masses. This is not an effect of evolution as the metallicities do not vary with redshift; it is most likely a property specific to the extremely UV-luminous WiggleZ galaxies.